PENINGKATAN HASIL BELAJAR SISWA TENTANG SISTEM PEREDARAN DARAH MANUSIA MELALUI MODEL PROBLEM BASED LEARNING DI KELAS V SDI NANO KABUPATEN TTS - Kase, Antonia; Koroh, Taty R.; Nawa, Netty E.A. (SINERGI : Jurnal Riset Ilmiah, 2024)
This research aims to improve the learning outcomes of class V SDI Nano students through the application of problem-based learning. The research subjects were class V students at SDI Nano with a total of 21 students. The type of research used is two-cycle classroom action research. The testing technique uses test techniques, observation and documentation which are used as data collection techniques. Based on the research results, it can be said that in the first cycle, student learning outcomes reached 28.5% with a class average of 60.7 and a success index of less than 80%. Completeness of student learning outcomes in cycle II was 90.4% with an average of 91.4 and the success index had reached 80%. Thus, it can be concluded that applying the problem based learning model can improve the science learning outcomes of class V SDI Nano students.